Differences in C-Reactive Protein Level Based on Clinical Severity and Outcome of COVID-19 Patients at RSUP Dr. M. Djamil Padang - Isnaniyah Usman; Irvan Medison; Deddy Herman (Jurnal Respirologi Indonesia, 2023)
Background: Inflammatory process in COVID-19 can increase inflammatory markers such as C-reactive protein (CRP), procalcitonin (PCT), and interleukin 6 (IL-6). The level of C-reactive protein describes the severity of viral infection. Several studies had been conducted to investigate the link between C-reactive protein level and the severity of COVID-19. The purpose of this study is to identify differences in C-reactive protein levels based on clinical degrees and outcomes of COVID-19 patients treated at RSUP by Dr. M. Jamil Padang.Methods: This is a retrospective cohort study that analyzed all COVID-19 patients treated at RSUP Dr. M. Djamil Padang. This study lasted from December 1st, 2021 and June 1st, 2022. The data was analyzed using univariate, bivariate, and confounding analysis. Bivariate analysis explored differences in C-reactive protein levels in clinical severity and patient outcomes for COVID-19. The Kruskal-Wallis test determined the difference between the CRP level and clinical severity, while the Mann-Whitney test determined the difference between the CRP level and length of stay and final hospitalization status. Confounding test was performed using multiple linear regression tests.Results: Majority of participants were women (51.0%) with range of age between 50–59 years (28.0%) and suffered from hypertension (46.0%). Less than half of them had secondary infection (49.0%). Majority of them had a critical clinical severity (75.0%) and length of stay ≤14 days (77.0%) and more than half were deceased (65.0%). C-reactive protein levels were higher in patients with critical clinical degrees (89.00 mg/L) compared to moderate (37.50 mg/L) and severe (23.00 mg/L), C-reactive protein levels in patients with long hospitalization ≤14 days (97.00 mg/L) was higher than >14 days (88.50 mg/L), and C-reactive protein levels were higher in patients who died (93.00 mg/L) than those who survived (68.00 mg/L).Conclusion: C-reactive protein levels differed significantly based on clinical severity, length of stay and end of stay status of COVID-19 patients.